Evolutionary dynamics of Oropouche virus in South America - Gutierrez, B; Wise, E; Pullan, S; Logue, C; Bowden, T; Escalera-Zamudio, M; Trueba, G; Nunes, M; Faria, N; Pybus, O (American Society for Microbiology, 2020)
The Amazon basin is home to numerous arthropod-borne viral pathogens that cause febrile disease in humans. Among these, Oropouche orthobunyavirus (OROV) is a relatively understudied member of the genus Orthobunyavirus, family Peribunyaviridae, that causes periodic outbreaks in human populations in Brazil and other South American countries. Although several studies have described the genetic diversity of the virus, the evolutionary processes that shape the OROV genome remain poorly understood. Here, we present a comprehensive study of the genomic dynamics of OROV that encompasses phylogenetic analysis, evolutionary rate estimates, inference of natural selective pressures, recombination and reassortment, and structural analysis of OROV variants. Our study includes all available published sequences, as well as a set of new OROV genome sequences obtained from patients in Ecuador, representing the first set of genomes from this country. Our results show differing evolutionary processes on the three segments that comprise the viral genome. We infer differing times of the most recent common ancestors of the genome segments and propose that this can be explained by cryptic reassortment. We also present the discovery of previously unobserved putative N-linked glycosylation sites, as well as codons that evolve under positive selection on the viral surface proteins, and discuss the potential role of these features in the evolution of OROV through a combined phylogenetic and structural approach.